Nudix hydrolase 14 influences plant development and grain chalkiness in rice - Liu, Yiran; Zhang, Wan; Wang, Youhang; Xie, Liling; Zhang, Qiuxin; Zhang, Jingjing; Li, Weiyan; Wu, Meifeng; Cui, Jingsong; Wang, Wenyi; Zhang, Zemin (Frontiers in Plant Science, 2022)
Nudix hydrolases (NUDX) can hydrolyze a wide range of organic pyrophosphates and are widely distributed in various organisms. Previous studies have shown that NUDXs are extensively involved in biotic and abiotic stress responses in different plant species; however, the role of NUDXs in plant growth and development remains largely unknown. In the present study, we identified and characterized OsNUDX14 localized in the mitochondria in rice. Results showed that OsNUDX14 is constitutively expressed in various tissues and most strongly expressed in mature leaves. In addition, repression of OsNUDX14 led to early flowering and a larger first leaf angle during the reproductive stage. In addition, OsNUDX14 affected grain chalkiness in rice. Furthermore, transcript profile analysis indicated that OsNUDX14 regulates lignin biosynthesis in rice. Six major haplotypes were identified by six OsNUDX14 missense mutations, including Hap1 to Hap_6. Accessions having the Hap_5 allele were geographically located mainly in South Asia with a low frequency in the Xian/indica subspecies. This study revealed that OsNUDX14 involved in plant development and grain quality regulation, providing a potential opportunity to optimize plant architecture and quality for crop breeding.